Improved photocatalytic efficiency of TiO2 by doping with tungsten and synthesizing in ionic liquid: precise kinetics-mechanism and effect of oxidizing agents - Raut, Sandesh S.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Environmental Science and Pollution Research, 2021)
The degradation of nitroaromatics/toxic energetic compounds contaminated water is a major cause of concern. W-doped TiO2 nanoparticles (NPs) were synthesized in ionic liquid, ethyl methyl imidazolium dicyanamide (EMIM-DCA) by a solvothermal method. The developed NPs were sintered at 500 degrees C and characterized by UV-Vis-DRS, FT-IR, FE-SEM, XRD, XPS, and BET techniques. The 30-40-nm-sized NPs were subjected to photocatalytic degradation of the toxic energetic compound, tetryl (2,4,6-trinitrophenylmethylnitramine) under UV-Vis light. Various operating parameters such as the effect of concentration of catalyst, pH of feed phase, oxidizing agents, and recycling of catalyst were studied in detail. For the first time, the degradation-mechanism pathway and kinetics of tetryl were evaluated. The degradation products were precisely analyzed by using HPLC, GC-MS, and TOC techniques. The USEPA has prescribed a drinking water limit of 0.02 mg L-1, and it was found that 0.5 g of 4% W-TiO2 could totally degrade tetryl (50 mg L-1) within 8 h. The kinetic rate constant of 4% W-TiO2 was 0.356 h(-1), whereas pure TiO2 showed 0.207 h(-1).
Keywords: Ionic liquid; Nitroaromatics; Photocatalysis; Recycling of catalyst; W-doped TiO2; wastewater